1983
DOI: 10.1007/bf00463614
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maturation of endocochlear potential and electrolyte composition of inner ear fluids in guinea pigs

Abstract: The maturation of the endocochlear potential (EP) and the inner ear fluid ionic composition were studied in fetal and neonate guinea pigs. The concentration of sodium and potassium in endolymph and perilymph approximated adult values more than 2 weeks before birth. Endolymph had acquired its specific ionic composition before the onset of cochlear microphonics (52-55 gestation days, results of other authors). Positive EP was recorded starting on day 62 of gestation. The EP rose fast to reach near adult level at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The guinea pigs showed abundant expression of ZO-1 both at the apical surfaces of the marginal cells and in the basal cell layer from PND 1 (Figures 6E and 6F). Morphometric data confirmed that on PND 1, the Cx26-positive area per area of spiral ligament reached the adult level in guinea pigs (no significant difference between PND 1 and PND 70) ( Figure 6I), which coincided with the endocochlear potential of neonatal and adult guinea pigs reported by Raphael et al (1983). Morphometric analysis for ZO-1 expression in the basal cell layer of the cochlea showed no significant difference between neonatal and adult guinea pigs of PND 70 ( Figure 6J).…”
Section: Cx26 and Zo-1 In The Cochlea Of Neonatal And Adult Guinea Pigssupporting
confidence: 78%
“…The guinea pigs showed abundant expression of ZO-1 both at the apical surfaces of the marginal cells and in the basal cell layer from PND 1 (Figures 6E and 6F). Morphometric data confirmed that on PND 1, the Cx26-positive area per area of spiral ligament reached the adult level in guinea pigs (no significant difference between PND 1 and PND 70) ( Figure 6I), which coincided with the endocochlear potential of neonatal and adult guinea pigs reported by Raphael et al (1983). Morphometric analysis for ZO-1 expression in the basal cell layer of the cochlea showed no significant difference between neonatal and adult guinea pigs of PND 70 ( Figure 6J).…”
Section: Cx26 and Zo-1 In The Cochlea Of Neonatal And Adult Guinea Pigssupporting
confidence: 78%
“…The morphological maturation of the fine structure of the stria vascularis of the guinea pig has been correlated with the subsequent onset of a positive endocochlear potential (EP) from E62 and a rapid elevation to the adult level at birth (Raphael et al 1983). In mice and rats, the EP increases between 8 and 13 days after birth and reaches its adult-like level at 16-17 days after birth (Rübsamen and Lippe 1998).…”
Section: Few Mesenchymal Cells Within the Spiral Ligament (Including mentioning
confidence: 99%
“…A good candidate for this model is the guinea pig since, similar to human neonates, they begin to hear in utero [Raphael et al, 1983] and guinea pigs have been used to access some aspects of postnatal auditory development [Dum, 1984;Walger et al, 1993]. The purpose of the present study was therefore to use clinical tests of auditory function in guinea pigs in order to document, under controlled conditions, the function of several parts of the auditory pathway -external ear, tympanic membrane (TM), ME, hair cells, auditory nerve and brainstem auditory pathway -longitudinally and comprehensively, until they reach adult-like values and to try to gain insight into the possible mechanisms of these changes.…”
Section: Introductionmentioning
confidence: 99%